APONTAMENTOS SOBRE O DESPERTAR DA ASSISTÊNCIA PSIQUIÁTRICA NACIONAL - Cavalcanti, Patrícia Barreto (Teoria Política & Social, 2009)
The aim of this study is to reconstruct, even if briefly, the evolutionary table about psychiatric assistance.The psychiatric assistance matter is extremely challenging in Brazil since its origin, despite the innovations and achievements observed through the last decades. In this study, we verify the lack of initiative from the government towards the psychiatric matter, as well as the use of out-of-date methods in the treatment received by the carriers of mental diseases. In the Brazilian mental health, already marked for critical elementary of the to overcrowd room and the inefficiency of the hospices, it is given for 1978 rollback the incipient organization of a new to look at on the Brazilian psychiatric assistance, where from now on, it is gone to foment in Brazil, the critical one not only to the structural situation of the lunatic asylum, but also and mainly to the authoritarian speech of erudition/power of psychiatry.